2020
DOI: 10.1038/s41598-020-78306-1
|View full text |Cite
|
Sign up to set email alerts
|

Spectral fingerprinting to evaluate effects of storage conditions on biomolecular structure of filter-dried saliva samples and recovered DNA

Abstract: Saliva has been widely recognized as a non-invasive, painless and easy-to-collect bodily fluid, which contains biomarkers that can be used for diagnosis of both oral and systemic diseases. Under ambient conditions, salivary biomarkers are subject to degradation. Therefore, in order to minimize degradation during transport and storage, saliva specimens need to be stabilized. The aim of this study was to investigate the feasibility of preserving saliva samples by drying to provide a shelf-stable source of DNA. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…By referring to the absorption intensity ratios of asymPO 2 /symPO 2 illustrated in Table 4 and taking into account the values associated with the hydrated phosphate group as indicated by Brogna et al [43], it is evident that a paradox effect was observed. This paradox effect consisted of the presence of dehydrated phosphate groups after 2 and 4 weeks of AlCl 3 administration.…”
Section: Discussionmentioning
confidence: 94%
“…By referring to the absorption intensity ratios of asymPO 2 /symPO 2 illustrated in Table 4 and taking into account the values associated with the hydrated phosphate group as indicated by Brogna et al [43], it is evident that a paradox effect was observed. This paradox effect consisted of the presence of dehydrated phosphate groups after 2 and 4 weeks of AlCl 3 administration.…”
Section: Discussionmentioning
confidence: 94%
“…Some previous studies used a different kind of saliva sample. Instead of a liquid saliva sample, some researchers prepared DSS samples and extracted DNA from them for various purposes [38][39][40]. Kisoi et al identified insertion/deletion polymorphisms of the angiotensin-converting enzyme (ACE) gene by PCR amplification using DNA from DSS samples [38].…”
Section: Saliva As a Good Source For Genetic Analysismentioning
confidence: 99%